Burrow Configuration and Utilization of the Blue-Spotted Mudskipper, Boleophthalmus boddarti Caught in Soc Trang, Vietnam - Dinh, Quang Minh; Giang, Nguyen Thi Tra; Duy, Ngo Nha Lam; Dong, Dang Hoang; Hau, Lam Trung (Journal of Fisheries and Environment, 2014)
The blue-spotted mudskipper, Boleophthalmus boddarti, is an important commercial fish species found in coastlines and estuaries in the Mekong Delta. This amphibious, mudflat inhabitant fish can directly respire air at mud surface. Despite its high economic value, information on biology and ecology, especially burrow structure is scarce. This study was carried out in order to understand burrow morphology and utilization purpose. The study was conducted for six months, from February to July 2013 in the Mekong Delta at Cu Lao Dung, Soc Trang province, Vietnam. The structure of the blue-spotted mudskipper burrow was studied by using resin castings on burrows in situ technique. Burrow structure of this species comprised one to two openings with "footmarks" made by its pectoral fins with one to two bulbous chambers. In general, burrow shapes were "I" and "U" types with one to two slightly slanting tunnels attaching the chambers together with some short cul-de-sac side branches. Moreover, the burrow had no mound at the opening. Results revealed that burrow structures have a strong relationship with fish size. The blue-spotted mudskipper uses a burrow as a place for foraging prey, living, refuge from predators, and spawning.